Hierarchy without Domination: Dalihan Natolu as a Relational Model of Justice and Religious Moderation among the Batak - Febri Kurnia Manoppo; Jenri Ambarita (Balai Penelitian dan Pengembangan Agama Jakarta, 2026)
This study examines the paradox of ‘dalihan natolu’, the Batak kinship system: how a hierarchy based on inherited roles produces egalitarian relationships whilst simultaneously underpinning religious moderation. This paradox is difficult to explain through John Rawls’s liberal theory of justice, which is grounded in individualism and the equality of basic freedoms, and thus regards ascriptive hierarchies as the antithesis of justice. Building on Rawls, this study interprets the dalihan natolu through the paradigm of relational justice and the theory of reciprocal exchange, asking: through what mechanisms and within what limits can different roles produce fairness and equality? Data were collected qualitatively through in-depth interviews, participatory observation and audiovisual content analysis. The findings reveal asymmetrical equality: rotating reciprocal obligations counterbalance an advantage in one relationship with a subordinate position in another, preventing hierarchies from solidifying into permanent domination. This mechanism transcends religious divides, whilst leaving gender tensions and the burden of customary obligations unresolved. Dalihan natolu challenges the liberal assumption that ascriptive roles preclude justice, whilst simultaneously promoting inter-religious, kinship-based religious moderation.